THE PRIMARY CARE PHYSICIAN ROLE IN PRIMARY STROKE PREVENTION. THE PLACE FOR ANTIHYPERTENSIVE THERAPY - S. Yu. Martsevich; N. P. Kutishenko (Кардиоваскулярная терапия и профилактика)
The article provides the definition of stroke, data on the mortality, risk factors. In detail, the role of antihypertension therapy is analized for primary stroke prevention, the significance of various antihypertension drugs from the evidence based point of view.